The Effect of Audit Quality on Fraud Reduction - Ahmed Sarwar Khan; Maryam Yousefi Nejad; Tahani Ali Hakami; Aza Azlina Md Kassim; Jaizah Othman (International Business and Accounting Research Journal, 2023)
The detection and investigation of financial fraud has become a worldwide concern, with auditors and accountants playing a pivotal role in identifying and examining such fraudulent activities. This role is especially crucial in developing countries, where fraudulent practices are more prevalent due to the lack of stringent regulations and supervision. The failure of some countries to adopt International Financial Reporting Standards (IFRS) has raised concerns in recent years. This study is a conceptual paper to explore the relationship between audit quality and fraud reduction. The study's results have important implications for developing countries, which have been demonstrated to be more vulnerable to fraud than developed countries. This research contributes to the current knowledge about the role of audit quality in mitigating fraud and highlights the need for auditors and accountants to be proactive in identifying and investigating financial fraud.